Preliminary ReportsLow dose rate brachytherapy using a tandem for cervical cancer - Mendez Javier, Aguirre; Poitevin Chacón, Adela (Journal of Contemporary Brachytherapy, 2009)
Purpose: To report the results of the Instituto Nacional de Cancerología México, of low dose rate brachytherapy for cervical cancer using only a tandem. A proportion of patients was treated with only a tandem, without ovoids, due to the distorted anatomy because of the tumour or previous external radiation, or sometimes due to physician preference. Material and methods: We report the results of 120 patients treated only with a tandem and the impact of this treatment on local control and survival from January 2005 to December 2006. The frequency of FIGO stage was: IIB 47%, IIIB 34%, IIA 9%, IIIA 4%, IB2 3% and IB1 3%. The median overall treatment time was 12 weeks. The value of the external beam radiation dose was 50-50.4 Gy in all patients and the value of the brachytherapy dose was 30 Gy given to point A. Results: Complete clinical response was 83% at the end of brachytherapy. Time to recurrence and frequency were: IB1 – 17 months (20%), IB2 – none, IIA – 8 months (8.3%), IIB – 11 months (40%) and IIIB – 14 months (25%). 10.8% of patients had a persistent tumour, 3.3% had progression during treatment in stage IIB. Survival in months was 26 months for stage IB1, 30 for IB2, 25 for IIA, 28 for IIB, 27 for IIIA and 24 for IIIB. 25% of patients died during follow-up. Conclusions: These preliminary results suggest that there is no significant difference between the treatment with brachytherapy using a tandem and ovoids or a tandem alone.